Design & Simulationof R Slotted Patch Antenna with EBG Substrates (International Journal of Scientific Research and Management (IJSRM), 2016)
This paper presents the design and simulation of rectangular& circular with EBG substrate using High Frequency Structure Simulator (HFSS).The two different configurations of broadband microstrip patch antenna, multistackedrectangular patch antenna &multistackedcircular patch antenna are analyzed. Return Loss & Gain are performance parameter. The substrate used in these two configurations is RT Duroid having dielectric constant 2.2.The result calculated is return loss of rectangular patch & circular patch with EBG substrates are -13.98 db & -43.4437 db and gain of rectangular patch &circular patch with EBG substrates are 5.7478 db& 10.4954 db respectively